The elements of user experience: user-centered design for the Web and beyond - Garrett, Jesse James
From the moment it was published almost ten years ago, Elements of User Experience became a vital reference for web and interaction designers the world over, and has come to define the core principles of the practice. Now, in this updated, expanded, and full-color new edition, Jesse James Garrett has refined his thinking about the Web, going beyond the desktop to include information that also applies to the sudden proliferation of mobile devices and applications. Successful interaction design requires more than just creating clean code and sharp graphics. You must also fulfill your strategic objectives while meeting the needs of your users. Even the best content and the most sophisticated technology won't help you balance those goals without a cohesive, consistent user experience to support it.